Implementasi Pembelajaran Berbasis Steam Melalui Proyek Kincir Angin Pada Anak Usia 5-6 Tahun Di TK Rancabogo - Resti Widiyanti; Dindin Abdul Muiz Lidinillah; Qonita Qonita (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
This study aimed to describe the implementation of Science, Technology, Engineering, Arts, and Mathematics (STEAM)-based learning through a windmill-making project for children aged 5–6 years at TK PGRI Rancabogo. The study employed a qualitative approach involving 10 children in Group B aged 5–6 years and one classroom teacher as the research participants. Data were collected through observation, interviews, and documentation. Data analysis followed the Miles, Huberman, and Saldaña model, including data condensation, data display, and conclusion drawing. The findings revealed that the windmill-making project successfully integrated the five STEAM components into a unified learning activity. The Science component was reflected in children's observations of the relationship between wind and the movement of the windmill. Technology was demonstrated through the use of various tools and materials during the construction process. Engineering emerged as children designed, assembled, tested, and refined the windmill to function properly. Art was represented through children's selection of colors and the creation of diverse windmill designs based on their creativity. Mathematics was integrated through activities involving the identification of geometric shapes, counting the number of sides, and comparing the speed of the windmill's rotation. Overall, the project provided meaningful, hands-on learning experiences that actively engaged children while integrating STEAM concepts in an authentic learning context